The Influence Of Promotion and Ease Of Access On Online Purchasing Decisions At Shopee: Case Study On Students Of The UKI Toraja Management Study Program - Mey E.Limbongan; Irmawati Mangguali (Proceeding of The International Conference on Economics and Business, 2022)
The purpose of this study was to determine the effect of promotion and ease of access on online purchasing decisions at Shopee (case study on students of the UKI Toraja Management study program). The type of research used is quantitative. The population in this study were students of the UKI Toraja Management Study Program Class of 2020 totaling 402 students. The number of samples calculated using Purposive Sampling technique obtained as many as 80 respondents. With the results of the study partially showing that the promotion variable has a positive and significant effect on purchasing decisions. This is evidenced by the tcount value of the promotion variable of 4.822 where this value is greater than the ttable value of 1.991. Partially, ease of access also has a positive and significant effect on purchasing decisions, with a tcount value of 4.238 where this value is greater than the ttable value of 1.991. The results of the study simultaneously show that the two independent variables in this study, namely the promotion variable and ease of access, have a positive and significant effect on the dependent variable, namely the purchase decision, this is evidenced by the fcount value of 34.683 where this value is known to be greater than the ftabel value of 3.12. Meanwhile, based on the coefficient of determination (R2), a value of 0.474 is obtained, meaning that the two independent variables affect the dependent variable by 47.4%, while the remaining 52.6% is influenced by other factors not included in this study.